Gender and power in modern feminist drama (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Modern feminist drama offers a powerful critique of patriarchal structures by foregrounding the complex dynamics of gender and power. Through innovative dramatic techniques, feminist playwrights challenge traditional representations of women, exposing the systemic inequalities that govern social, political, and cultural life. This study examines how modern feminist drama interrogates dominant power relations, highlights women’s experiences of oppression and resistance, and redefines female identity and agency. By portraying women’s struggles against marginalization, domestic confinement, sexual exploitation, and institutionalized control, feminist drama becomes a site of ideological resistance and social transformation. The plays reveal the intricate intersections of gender, class, race, and sexuality, demonstrating how power operates across multiple social levels. Moreover, feminist dramatists reimagine women not as passive victims but as active agents capable of self-awareness, rebellion, and empowerment. Through character development, symbolic representation, and alternative narrative structures, feminist drama dismantles patriarchal norms and offers new possibilities for equality and justice. The study concludes that modern feminist drama significantly contributes to feminist discourse by redefining gender roles, questioning established power hierarchies, and promoting critical awareness of women’s rights and liberation.